Bevacizumab treatment for meningiomas in NF2: a retrospective analysis of 15 patients. - Fabio P Nunes (Public Library of Science (PLoS), 2013)
Bevacizumab treatment can result in tumor shrinkage of progressive vestibular schwannomas in some neurofibromatosis 2 (NF2) patients but its effect on meningiomas has not been defined. To determine the clinical activity of bevacizumab against NF2-related meningiomas, we measured changes in volume of meningiomas in NF2 patients who received bevacizumab for treatment of progressive vestibular schwannomas. A radiographic response was defined as a 20% decrease in tumor size by volumetric MRI analysis. In addition, we determined the expression pattern of growth factors associated with tumor angiogenesis in paraffin-embedded tissues from 26 unrelated meningiomas. A total of 48 meningiomas in 15 NF2 patients were included in this study with a median follow up time of 18 months. A volumetric radiographic response was seen in 29% of the meningiomas (14/48). Tumor shrinkage was not durable: the median duration of response was 3.7 months and the median time to progression was 15 months. There was no significant correlation between pre-treatment growth rate and meningioma response in regression models. Tissue analysis showed no correlation between tumor microvascular density and expression of VEGF pathway components. This data suggests that, in contrast to schwannomas, activation of VEGF pathway is not the primary driver of angiogenesis in meningiomas. Our results suggest that a minority of NF2-associated meningiomas shrink during bevacizumab therapy and that these responses were of short duration. These results are comparable to previous studies of bevacizumab in sporadic meningiomas.